The commissioning of a test facility for the calibration of anemometers - J. J. Van Rensburg (The Southern African Institute of Mining and Metallurgy, 1975)
The commissioning of a test facility for the calibration of anemometers by J. J. VAN RENSBURG (Student Member). After the erection of a commercially produced open-jet wind tunnel for the calibration of the anemometers used in mine ventilation, the wind tunnel was calibrated for routine use. There is a choice of five orifice plates. which, together with a variable-speed fan, can give a measurable range of air velocities in the test section from about 0,05 to 35 m/so The orifice plates were calibrated against a standard pitot tube, and it is now necessary only to measure the pressure drop across an orifice plate and to read off, from a set of graphs, the true outlet velocity in the test section. The paper describes the underlying theory and the test results.